Upgrading the global garment industry internationalization, capabilities and sustainability - Rana, Mohammad B. (New Perspectives on the Modern Corporation Ser.)
This timely book focuses on the upgrading of firms within the global garment industry, examining how garment manufacturers and retailers in different countries internationalize, develop their capabilities and enhance their sustainability. It highlights the important role the global garments industry plays in the socio-economic development and environmental outcomes of emerging economies.